2001
DOI: 10.1590/s0036-46652001000100004
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of acute diarrhea among children in Ribeirão Preto-SP, Brazil

Abstract: To study the main enteropathogens causing diarrhea in the region of Ribeirão Preto regarding serogroups and serotypes, the feces of 1836 children under 10 years old, from both sexes, attack of acute gastroenteritis, were analysed during a period of 4 years in Adolfo Lutz Institute - Ribeirão Preto, SP. The pathogens identified by standard methods were the following: Escherichia coli, Salmonella spp., Shigella spp., Campylobacter spp., Yersinia spp., and Cryptosporidium spp. Positive samples were 22.8% (419) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
15

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 11 publications
1
17
1
15
Order By: Relevance
“…This is in contrast with studies from other places in Brazil, which detected S. sonnei as the most frequent serogroups: Ribeirão Preto-SP (Medeiros et al 2001), and Salvador-BA (Diniz- Santos et al 2005). However, our finding is consistent with other reports from Northeastern Brazil (Lima et al 1995), Porto Alegre-RS (Santos et al 1997), and São José do Rio Preto-SP (Almeida et al 1998), and those from other Latin America developing countries such as Argentina (Merino et al 2004), Peru (Jones et al 2004), and Chile (Fulla et al 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast with studies from other places in Brazil, which detected S. sonnei as the most frequent serogroups: Ribeirão Preto-SP (Medeiros et al 2001), and Salvador-BA (Diniz- Santos et al 2005). However, our finding is consistent with other reports from Northeastern Brazil (Lima et al 1995), Porto Alegre-RS (Santos et al 1997), and São José do Rio Preto-SP (Almeida et al 1998), and those from other Latin America developing countries such as Argentina (Merino et al 2004), Peru (Jones et al 2004), and Chile (Fulla et al 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…Estudos realizados em diferentes estados no Brasil têm demonstrado uma prevalência de Cryptosporidium spp em crianças (0 a 12 anos de idade) de 4,2%, 3,3% e 1,8% em Uberlândia (MG) 11 , Rio de Janeiro (RJ) 30 e Ribeirão Preto (SP) 22 , respectivamente.…”
Section: Discussionunclassified
“…19,20,[22][23][24][25][26][27][28][29][30]32,33 Despite the number of reports indicating the association of this parasite with diarrhea in different settings and the presence of this parasite in the environment in different regions of this country, only 1 molecular assessment has been previously performed, in clinical samples collected in Fortaleza, Brazil. 47 We used previously described molecular tools 39,41,42 to analyze samples collected from children attending a day care at the Hospital das Clínicas, from March to May 2001, during which an outbreak of cryptosporidiosis took place.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in different regions of Brazil have shown that Cryptosporidium sp is associated with symptomatic intestinal disease in HIV infected individuals and in children suffering of acute diarrhea, including those attending day care. [22][23][24][25][26][27][28] Environmental contamination with Cryptosporidium oocysts has been observed in rivers and public water reservoirs serving different regions in Sao Paulo. [29][30][31][32] Nevertheless, no massive cryptosporidiosis outbreaks associated with consumption of water in these regions have been reported.…”
Section: Introductionmentioning
confidence: 99%